Study on Artifacts Elimination for Three-Dimensional Interaction Virtual Reality Corridors - Xiaofan Liu; Jinye Wang; Wenjun Zheng; Ying Chen; Er Wu (IEEE Access)
Our team had proposed a Ground Control Points-free three-dimensional interactive virtual reality (3DIVR) for building scene models. However, during the actual scene model construction, we found that the blinking-artifacts and shadow-artifacts generated by light reflection and occlusion have potential effects on corner point detection and also affect the accuracy of 3DIVR. Therefore, this paper proposes a generalized artifact elimination method for eliminating blinking-artifacts and shadow-artifacts based on previous studies. The method first identifies blinking-artifacts by detecting blinking-pixels and calculating the difference values during blinking. Then, it compares these difference values with the blinking threshold. Based on the blinking threshold, it distributes compensation values to the blinking-artifacts. Finally, it smooths the deviated data after blinking-artifact elimination. Additionally, the method eliminates shadow-artifacts by improving the local brightness balance across the three color channels. Since the most important effect of light on the image is on the brightness layer, we used a set of brightness images for a detailed implementation of the principle. And then, we used the three sets of colors to verify the effectiveness of the method proposed in this paper, comparing them with the adjusted brightness method and the adjusted background method. Compared with another method, the results obtained by the method proposed in this paper exhibit two key advantages. On the one hand, they exhibit better visual quality. On the other hand, the mean value and entropy value of our results are superior to those of the other method. Currently, our team has incorporated this method into our self-developed 3DIVR system, which, in the future, will provide better assistance to related researchers.